Theoretical Hydrodynamic Modeling of the Fluidized Bed Photoreactor (FBP) Using Computational Fluid Dynamics (CFD): Fluidization Conditions for TiO2-CuO Immobilized on Beach Sand Granules - Ricardo Solano; Miguel Mueses; Adriana Herrera (Modelling and Simulation in Engineering)
The flow regime is essential in the photoreactor’s performance in pollutant degradation in the aqueous medium, especially in fluidized systems. Therefore, this study is focused on determining the fluidization conditions of a granular catalyst based on TiO2-CuO nanoparticles (1 wt.% CuO) immobilized on beach sand granules using an FBP photoreactor. COMSOL Multiphysics 6.0 was employed for inlet velocities between 0.1 m/s and 1.0 m/s, mainly from the Reynolds averaged Navier–Stokes (RANS) turbulence model and the Stokes drag law. The results indicated that the average velocities in the annular section are much higher (4.11ut and 5.42ut) than the required particle terminal velocity. Moreover, the pressure contour lines revealed that these flow velocities do not represent excessive pressures in the concentric cylinders, with maximum gauge pressures of 740.52 Pa and 1310 Pa for inlet velocities Uo=0.75 and 1.0 m/s, respectively. Finally, it was determined that the Reynolds number adjusted (Repf) values lower than or equal to 1.37×10−3 allow high fluidization after 2 seconds. This information makes it possible to adapt and assemble the FBP equipment for future photocatalytic evaluation.